DEHYDROXYLATION, PROTON MIGRATION, AND STRUCTURAL CHANGES IN HEATED TALC: AN INFRARED SPECTROSCOPIC STUDY - Zhang M.; Hui Q.; Lou X.-J.; Redfern S.A.T.; Salje E.K.H.; Tarantino S.C. (My University, 2006)
The high-temperature dehydroxylation and structural change of talc, Mg3(Si2O5)2(OH)2, has been investigated in detail using infrared (IR) spectroscopy. The data (in the region of 20-12000 cm-1) on quenched samples show that absorptions from structurally incorporated OH and OD, as well as NH4-like species, have similar temperature dependences in dehydroxylation. The OH species exhibit weak variation in frequency on heating, which is inconsistent with thermally induced weakening of O-H bonds. Dehydroxylation in talc is a complex process that involves proton migrations and formation of new OH species. Additional fundamental OH bands near 3665 and 3745 cm-1 became detectable near 900 °C. On further heating the former disappear near 1200 °C, whereas the latter became undetectable near 1350 °C. The occurrence of CO2 is observed in samples quenched between 600 and 1250 °C. The phonon spectrum (20-1500 cm-1) of the dehydroxylate (obtained by annealing the sample at 1000 °C) gives features significantly different from that of talc, indicating the loss of the original layer structure. The IR data imply that the talc dehydroxylate consists of disordered SiO2 and enstatite (MgSiO3). Although MgSiO3 exists dominantly in the form of orthoenstatite, the characteristic bands of clinoenstatite phase are found to coexist in the samples treated at 1000 °C. The IR data from in situ measurements show that protons become mobile at temperatures below the dehydroxylation and an extra OH species near 3500 cm-1 develops on heating. This new species is not quenchable, and it decreases intensity on cooling and disappears at room temperature. The in situ results also indicate external carbon-related substances can diffuse into talc during dehydroxylation.
Keywords: CO2; DEHYDROXYLATION; ENSTATITE; INFRARED SPECTROSCOPY; NH4; OD; OH; TALC